(untitled) (Research, Society and Development, 2020)
Obstetric interventions and the mastery of the female body transfer to the scenario of childbirth the care model surrounded by technology, with consequent loss of the woman’s role in the phenomenon of parturition. In this context, Brazil has started to direct public policies with a focus on the humanization of childbirth and women’s autonomy, in order to reduce interventional practices, such as the Labor and Birth Humanization Program. Such changes have provided the insertion of Nursing as an important agent of transformations, since it has as its essence a holistic care based on non-interventional practices, however, it is still verified that the role of women in childbirth is not a hegemonic reality, causing damage to maternal and neonatal health. The aim of this study is to favor the role of women in childbirth through health education in front of the nursing team working in childbirth care in a public maternity in the state of Amapá. This is a qualitative-quantitative approach research, because it allowed the understanding of meanings considering the subjectivities present, while it allowed classifying and analyzing them. The intervention allowed the team to reflect on the theme, and it is expected that qualifications in obstetric care will be promoted, as well as that the process of health education for SUS workers will become more concrete in the institution studied.